Molecular characterization of induced mutation of jewawut (Setaria italica ssp. italica) from Buru Island, Indonesia using SRAP - KUSUMADEWI SRI YULITA; RIDWAN RIDWAN (Biodiversitas Journal of Biological Diversity, 2018)
Yulita KS, Ridwan. 2018. Molecular characterization of induced mutation of jewawut (Setaria italica ssp. italica) from Buru Island, Indonesia using SRAP. Biodiversitas 19: 1160-1168. Jewawut (Setaria italica ssp. italica) or foxtail millet is minor crops domesticated and consumed only in few parts of Sulawesi, Maluku and East Nusa Tenggara, while in other region such as Java, it is known as food for bird despite the fact that jewawut is rich in fiber. The utilization of jewawut as an alternative crop was limited due to their small size of seeds as well low yield. An effort to improve the potency of jewawut as an alternative food is through genetic improvement by induced mutation. This present study was aimed to determinate mutant of jewawut from Buru Island irradiated by gamma rays as potential genotype to produce high grain yield. Two variants of jewawut were recorded from Buru Island, red and yellow variant each referring to the colour of their seeds. Samples were consisted of 26 red and 24 of yellow variant. Mutant was detected by molecular characterization using SRAP marker. UPGMA cluster analysis was also performed to ensure the position of mutant within the UPGMA dendrogram against the control samples. Mutant with the most distinct genyotypes for yellow variant are accession O1O2#10 treated in 100 Gy and O1E1#10 treated in 200 Gy gamma radiation, whereas in the red variant are accessions O2C4#13 treated in 50 Gy and O2E4#6 treated in 200 Gy gamma radiation. All the mutants have random agronomic performances relative to controls. Mutants with potential high grain yield are O2B2#14 treated in 25 Gy for the red variant, and this should be used as a candidate to develop superior genotype.